RE-BUSCANDO O IN-FINITOUMA: ANÁLISE DE LIÇÕES DE ESPAÇO DE ROBERTO PONTES - Gomes, Márcio dos Santos (Revista de Letras, 2017)
RE-BUSCANDO O IN-FINITOUMA: ANÁLISE DE LIÇÕES DE ESPAÇO DE ROBERTO PONTES